The effect of religiosity and cultural conservatism on digital privacy concerns: A comparative longitudinal study of five Arab countries - Haider, Waseem; Martin, Justin D.; Farooq, Ali; Salminen, Joni; Jansen, Bernard J. (SAGE Publications, 2026)
This study examines the influence of religiosity and cultural conservatism on digital privacy concerns (DPC) among internet users from five Arab countries. Across four waves (2017–2022), in-person and telephone interviews captured responses from 18,160 adults in Saudi Arabia, Tunisia, Lebanon, Qatar, and the United Arab Emirates (UAE). We fitted random-intercept multilevel regressions that nest individuals within country-by-wave clusters, allowing the slope of religiosity to vary across these clusters. We hypothesized religiosity would positively predict DPC, and results confirmed that. This study also hypothesized that the positive relationship between religiosity and DPC would be stronger among respondents reporting higher cultural conservatism, though this hypothesis was not supported. Instead, religious and progressive respondents reported greater DPC than other respondents, suggesting that religious progressives, living as they do in culturally conservative locales, may experience tension between religious and progressive beliefs, which leads to heightened DPC.